Bacteriological Outline and Antibiogram of Uropathogens: A Study at a Tertiary Care Centre - Vani Majji (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Background: Urinary tract infections (UTIs) are one of the most common infections, both in the community and in healthcare worldwide. The clinical spectrum of UTI can range from asymptomatic bacteriuria to severe forms like emphysematous pyelonephritis and sepsis. UTIs are a cause of significant morbidity and mortality requiring urgent antibiotic treatment. However, there is widespread antibiotic resistance from the bacterial causes, necessitating regular surveillance for drug-resistant bacteria and their antibiograms. Objective: The aim of this study is to isolate and identify various bacterial causes of UTIs and determine their antibiotic susceptibility patterns. Methods: A total of 5017 urine samples were analyzed from January 2021 to December 2022. Out of these 1014 samples were positive. Identification of the pathogen and anti-microbial sensitivity was done using the Automated system, Vitek 2 compact (Biomereiux). Results: Culture positivity in this study was 20%. Gram-negative bacteria were predominantly isolated (79.7%), including Escherichia coli (52.8%) and Klebsiella aerogenes (14.2%). Enterococcus faecalis was the most common Gram-positive bacterium isolated. Antibiotic susceptibility pattern among gram-negative bacilli has shown maximum sensitivity to Colistin and Fosfomycin followed by Carbapenems (Imipenem, Meropenem & Ertapenem), Amikacin and Beta lactam-beta-lactamase inhibitor (BL-BLI) combination drugs. Out-patient department (OPD) samples were found to be more susceptible to antimicrobials than In-patient department (IPD) samples. Maximum resistance was seen against Ciprofloxacin and Ceftriaxone. Klebsiella and Pseudomonas isolates were found to be more resistant when compared to E. coli. isolates were more sensitive to Nitrofurantoin (87%) than Klebsiella (22%). Carbapenem resistance was seen in 50% of the Inpatient isolates of Klebsiella pneumoniae and 36% of Inpatient isolates of Pseudomonas aeruginosa. Few isolates of K. pneumoniae & P. aeruginosa were found to be resistant even to Colistin. In order to prevent the development of resistance, antibiotic susceptibility patterns must be continuously and periodically evaluated to select the appropriate regimen to treat UTI and to avoid complications.